IKHTIAR HIMPUNAN MAHASISWA ISLAM CABANG JAMBIDALAM MEMBENTUK BUDAYA MEMBACA DI KALANGAN MAHASISWA SERTA AKTIVIS - Harahap, Pandu Wijaya Nagari (SINERGI : Jurnal Riset Ilmiah, 2025)
ABSTRACK This writing aims to determine the pattern and culture of reading among HMI Jambi Branch organizations and to complete the requirements as a candidate for General Chair of the Jambi Branch of HMI. positive encouragement to respond to the dynamics of the times both now and in the future. One of the weapons prepared to respond to the upheavals of the times is to foster a reading culture among activists. Efforts that must be made to create a reading culture include the establishment of discussion forums, scientific studies, book reviews and other activities that can provide stimulus to HMI cadres to create a reading culture. The reading culture is an effort to contextualize the objectives of HMI contained in article 4 of the Articles of Association "The development of academic people, creators, servants, who breathe Islam and are responsible for the realization of a just and prosperous society that is blessed by Allah Subhanahu Wata'ala." Forming a reading culture among Jambi Branch HMI Activists certainly has the main goal, namely wanting to restore the struggle and identity that has been lost from civilization in the academic world and the organizational world, especially the Jambi Branch HMI Organization, which incidentally is students from Batanghari University, Jambi University, Sulthan Thaha Saifuddin State Islamic University Jambi, Muhammadiyah University Jambi and other campuses. This type of writing is descriptive research with a qualitative approach. Data collection techniques through observation, interviews and documentation. The results of the writing show that the majority of HMI Jambi Branch activists have abandoned the culture of reading as the main characteristic and character that must be maintained. As an organization whose cadre base is Muslim students, its main goal is to be able to produce cadres with academic, religious and humanitarian qualities. The HMI organization as a gathering place for Islamic students throughout the archipelago, always provides ABSTRAK Penulisan ini bertujuan untuk mengetahui pola dan budaya membaca di kalangan organisatoris HMI Cabang Jambi serta melengkapi persyaratan sebagai kandidat Calon Ketua Umum HMI Cabang Jambi. Jenis penulisan ini adalah penelitian deskriptif dengan pendekatan kualitatif. Teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Hasil penulisan menunjukkan bahwa sebagian besar kalangan aktvivis HMI Cabang Jambi sudah meninggalkan budaya membaca sebagai ciri dan karakter utama yang harus dipertahankan. Sebagai organisasi dengan basis kadernya adalah mahasiswa muslim, maka tujuan utamanya adalah mampu melahirkan kader-kader yang berkualitas akademis, religius, dan humanitas. Organisasi HMI sebagai wadah berkumpulnya mahasiswa islam se-nusantara, selalu memberikan dorongan yang positif guna merespon dinamika zaman baik di masa kini dan di masa yang akan datang, salah satu senjata yang dipersiapkan guna merespon pergolakan zaman adalah dengan menumbuhkan budaya membaca dikalangan aktivisnya. Upaya-upaya yang harus dilakukan guna membentuk budaya membaca adalah dengan dibentuknya forum-forum diskusi, kajian ilmiah, bedah buku, dan kegiatan lainnya yang dapat memberikan stimulus kepada kader HMI guna melahhirkan budaya membaca. Budaya membaca adalah sebagai upaya mengkontekstualisasikan tujuan HMI yang terkandung dalam pasal 4 Anggaran Dasar “Terbinanya Insan Akademis, Pencipta, Pengabdi, yang bernafaskan Islam dan bertanggungjawab atas terwujudnya masyarakat adil makmur yang di ridhoi Allah Subhanahu Wata’ala”. Membentuk budaya membaca di kalangan Aktivis HMI Cabang Jambi tentunya memiliki tujuan utama yaitu ingin mengembalikan khittah perjuangan dan identitas yang telah hilang dari peradaban dunia akademis dan dunia organisatoris khususnya Organisasi HMI Cabang Jambi yang notabenenya adalah Mahasiswa/i Universitas Batanghari, Universitas Jambi, Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Universitas Muhammadiyah Jambi dan Kampus lainnya.